2011
DOI: 10.1002/jcb.23004
|View full text |Cite
|
Sign up to set email alerts
|

Roscovitine, a selective CDK inhibitor, reduces the basal and estrogen‐induced phosphorylation of ER‐α in human ER‐positive breast cancer cells

Abstract: Roscovitine (ROSC), a selective cyclin-dependent kinase (CDK) inhibitor, arrests human estrogen receptor-α (ER-α) positive MCF-7 breast cancer cells in the G(2) phase of the cell cycle and concomitantly induces apoptosis via a p53-dependent pathway. The effect of ROSC is markedly diminished in MCF-7 cells maintained in the presence of estrogen-mimicking compounds. Therefore, we decided to examine whether ROSC has any effect on the functional status of the ER-α transcription factor. Exposure of MCF-7 cells to R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
20
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 81 publications
(86 reference statements)
4
20
0
Order By: Relevance
“…Our findings suggest that the reduction in ERα levels in the resistant cells is due to both transcriptional and post-translational effects by roscovitine. Our data corroborate data from a recent study that demonstrated a reduction in ERα levels in MCF7 cells after roscovitine treatment, which possibly occurred through the inhibition of CDK7 [53]. As many endocrine therapy-resistant cells retain expression and functionality of ERα, the ability of roscovitine to down regulate the ERα axis, may also have contributed to its ability to curb the progression of the resistant cells.…”
Section: Discussionsupporting
confidence: 90%
“…Our findings suggest that the reduction in ERα levels in the resistant cells is due to both transcriptional and post-translational effects by roscovitine. Our data corroborate data from a recent study that demonstrated a reduction in ERα levels in MCF7 cells after roscovitine treatment, which possibly occurred through the inhibition of CDK7 [53]. As many endocrine therapy-resistant cells retain expression and functionality of ERα, the ability of roscovitine to down regulate the ERα axis, may also have contributed to its ability to curb the progression of the resistant cells.…”
Section: Discussionsupporting
confidence: 90%
“…Decreases in ER expression or transcriptional activity provide a potential mechanism for this effect. Phosphorylation by CDK2 activates ERa, and this effect is enhanced by CDK7 (47), so that inhibition of these CDKs inhibits ERa transcriptional activity (44,48). In addition, the CDK inhibitor roscovitine decreases ERa expression (44,48).…”
Section: Discussionmentioning
confidence: 99%
“…More than 140 CDK inhibitors have been described, of which 10 are currently undergoing phase 1 or phase 2 clinical trials as anti-cancer agents [19]. Roscovitine (also known as CYC202 or seliciclib) is a 2,6,9-tri-substituted purine that is in late phase 2 trials for non-small cell lung cancer and nasopharyngeal cancer [14, 15, 19]. Roscovitine has demonstrated selectivity for certain kinases, including CDKs-1, -2, -5, -7, and –9; other potentially attractive features are its oral bioavailabilty and more modest toxicity than other such inhibitors [19].…”
Section: Discussionmentioning
confidence: 99%
“…We have previously investigated the neuroprotective potential of a relatively selective CDK inhibitor roscovitine, which is currently being evaluated clinically for the treatment of certain cancers [1416]. Roscovitine attenuates CCA, progressive neurodegeneration, and neurological dysfunction in several models of TBI [17, 18].…”
Section: Introductionmentioning
confidence: 99%